Chemoenzymatic synthesis of enantiopure structured triacylglycerols and palm olein alcoholysis by lipase - Rakel Sæmundsdóttir 1984- (2010)
In recent years enzymes have gained increased attention as practical biocatalysts with application both in the industry as well as lab-scale synthesis. Lipases have been studied widely, but our research focused on utilising them in the asymmetric synthesis of structured triacylglycerols (TAG) and palm olein alcoholysis. A six step chemoenzymatic process was developed for synthesis of ABC type TAG. Starting from enantiopure solketal 1-O-benzylglycerol was synthesized. Pure stearic acid was then introduced to the primary hydroxyl group by immobilized Candida antarctica lipase (CAL), followed by catalytic hydrogenation of the benzyl protective group to afford a regioisomerically pure 1-MAG. A subsequent introduction of a second different saturated fatty acid (varying from acetic acid to palmitic acid), exclusively to the vacant primary hydroxyl group by CAL, afforded a non-symmetric regioisomerically pure 1,3-DAG that was finally acylated at the mid position with pure docosahexaenoic acid (DHA) by the EDCI coupling reaction. Both antipodes of the enantiopure TAG described above have been synthesized in good to excellent yields (63-97%) and fully characterised by traditional organic synthesis analysis. Ten lipases were tested for their ability to catalyse ethanolysis of palm olein at a good conversion rate and selectivity towards saturated fatty acids that would enable separation of the saturated and unsaturated fatty acids in the oil. After some initial screening, two lipases were selected for further testing. A 1H NMR based method was developed for determining the conversion and to provide further insight into the progress of the ethanolysis reaction. The University of Iceland Research Fund and Novozymes AS